H+‐pyrophosphatase from Salicornia europaea confers tolerance to simultaneously occurring salt stress and nitrogen deficiency in Arabidopsis and wheat. (11th June 2015) - Lv, Sulian; Jiang, Ping; Nie, Lingling; Chen, Xianyang; Tai, Fang; Wang, Duoliya; Fan, Pengxiang; Feng, Juanjuan; Bao, Hexigeduleng; Wang, Jinhui; Li, Yinxin
Abstract: High salinity and nitrogen (N) deficiency in soil are two key factors limiting crop productivity, and they usually occur simultaneously. Here we firstly found that H + ‐PPase is involved in salt‐stimulated NO3 − uptake in the euhalophyte S alicornia europaea . Then, two genes (named SeVP1 and SeVP2 ) encoding H + ‐PPase from S .  europaea were characterized. The expression of SeVP1 and SeVP2 was induced by salt stress and N starvation. Both SeVP1 or SeVP2 transgenic A rabidopsis and wheat plants outperformed the wild types (WTs) when high salt and low N occur simultaneously. The transgenic A rabidopsis plants maintained higher K + /Na + ratio in leaves and exhibited increased NO3 − uptake, inorganic pyrophosphate‐dependent vacuolar nitrate efflux and assimilation capacity under this double stresses. Furthermore, they had more soluble sugars in shoots and roots and less starch accumulation in shoots than WT. These performances can be explained by the up‐regulated expression of ion, nitrate and sugar transporter genes in transgenic plants. Taken together, our results suggest that up‐regulation of H + ‐PPase favours the transport of photosynthates to root, which could promote root growth and integrate N and carbon metabolism in plant. This work provides potential strategies for improving crop yields challenged by increasing soil salinization and shrinking farmland. Abstract : High salinity and nitrogen (N) deficiency which usually occur simultaneously in soil are two key factors limiting crop productivity. Here we firstly found that H + ‐pyrophosphatase (H + ‐PPase) is involved in salt stimulated NO3 − uptake in the euhalophyte Salicornia europaea, and up‐regulation of H + ‐pyrophosphatase confers tolerance to simultaneously occurring salt stress and nitrogen deficiency in A rabidopsis and wheat. This work provides alternative strategy for improving crop yields challenged by increasing soil salinization and shrinking farmland via H + ‐PPase regulation.